Factors influencing adherence to positive airway pressure therapy in stroke patients with obstructive sleep apnea: a cross-sectional study - Yu, Wen-Yi; Xu, Li-Wen; Sun, Shu-Tong; Zheng, Yi-Xi; Jing, Tian-Yu; Xu, Gang; Tang, Tie-Yu; Chu, Cheng (Frontiers in Neurology, 2025)
BackgroundPositive Airway Pressure (PAP) treatment is the recommended initial approach for moderately severe obstructive sleep apnea patients. Its efficacy is contingent upon patient compliance, yet compliance studies in combined stroke and obstructive sleep apnea (OSA) patients have demonstrated lower rates of compliance, and most of the influencing factors are unregulated. This study aimed to explore short-term respiratory therapy compliance status among stroke patients with obstructive sleep apnea and identify modifiable influencing factors to improve compliance and create personalized plans.MethodsThis study was conducted among 254 stroke patients with OSA. Data were collected using standardized questionnaires, including the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), and Self-Efficacy Measure for Sleep Apnea (SEMSA). Polysomnography (PSG) was used to assess objective sleep parameters. Logistic regression analysis was performed to identify predictors of PAP adherence.ResultsThe overall compliance rate of stroke patients with OSA was 27.2%, and self-efficacy in patients with stroke combined with OSA (perceived risk (OR = 2.23, 95% CI = 1.74 2.83), expected effect of treatment (OR = 1.23, 95% CI = 1.23 1.4), self-assessment (OR = 1.17, 95% CI = 1.06 1.30), total score on the Health Beliefs Scale (OR = 1.20, 95% CI = 1.13 1.26)), objective sleep condition (total sleep duration (OR = 1.00, 95% CI = 1.00 1.01), sleep efficiency (OR = 1.00, 95% CI = 1.00 1.04)) (OR = 1.01, 95% CI = 1.00 1.02), N1 phase duration (OR = 1.01, 95% CI = 1.00 1.01)), OSA severity (AHI (OR = 1.04, 95% CI = 1.02 1.06), and longest hypoventilation time (s) (OR = 1.02, 95% CI = 1.00 1.03), and oxygen desaturation ≥3 index (ODI) (OR = 1.03, 95% CI = 1.01 1.05) were the risk factors affecting their PAP treatment.ConclusionPatients with stroke combined with OSA have poorer compliance to PAP treatment (27.2%) compared with the general population, and this compliance is closely related to self-efficacy, objective sleep, and the severity of OSA. In the future, we can combine with the Health Belief Models to formulate an individualized intervention plan based on patients’ self-efficacy.